Depersonalization disorder in pre-adolescent child of acute disseminated encephalomyelitis - Khairkar, Praveen; Bang, Govind; Agarwal, Amit; Lakhkar, Bhavna; Jagzape, Tushar (Journal of Pediatric Neurology, 2010)
Acute disseminated encephalomyelitis is a rare inflammatory demyelinating entity affecting central nervous system. This immune mediated disease shows variable presentation of motor, sensory, visual, gait, and memory disturbances that usually follow vaccinations or some viral or bacterial infections. Review of literature showed few case reports of acute disseminated encephalomyelitis presenting as psychiatric disorders like acute Korsakoff's syndrome, conversion disorder and acute psychosis. However, none of them had been reported in pre-adolescent age group to the best of our knowledge. We herein report the first case of depersonalization disorder in a child suffering from acute disseminated encephalomyelitis.
Keywords: Depersonalization disorder; acute disseminated encephalomyelitis; pre-adolescence; neuropsychiatry